a-Actinin-3 and performance - Yang, N.; Garton, F.; North, K. (Genetics and Sports, 2009)
The human sarcomeric a-actinins (ACTN2 and ACTN3) are major structural components of the Z line in skeletal muscle; they play a role in the maintenance of sarcomeric integrity and also interact with a wide variety of structural, signaling and metabolic proteins. ACTN2 is expressed in all muscle fibers, and expression of ACTN3 is restricted to the type 2 (fast glycolytic) fibers that are responsible for forceful contraction at high velocity. There is a common stop codon polymorphism R577X in the ACTN3 gene. Homozygosity for the R577X null-allele results in the absence of a-actinin-3 in fast muscle fibers with frequencies that vary from < 1% in Africans to ~18% in Caucasians. A number of association studies have demonstrated that the ACTN3 R577X genotype influences athletic performance in Caucasians; the frequency of the XX genotype is significantly lower than controls in sprint athletes, and it appears that a-actinin-3 deficiency is detrimental to sprint performance. In the general population, the ACTN3 genotype contributes to the normal variations in muscle strength and sprinting speed. In an Actn3 knockout mouse model, a-actinin-3 deficiency is associated with a shift in the characteristics of fast, glycolytic 2B muscle fibers towards a slow phenotype, with decreased muscle mass and fiber diameter, slower contractile properties, increased fatigue resistance, and an increase in oxidative enzyme activity. The shift towards a more efficient oxidative metabolism may underlie the selective advantage of the X-allele during evolution. In turn, the shift towards a `slow` muscle phenotype in fast muscle fibers likely explains why loss of a-actinin-3 is detrimental to sprint performance. (Autorreferat)